(untitled) (The Review of Diabetic Studies, 2025)
Within the framework of the Sustainable Development Goals (SDGs), this research addresses the need to strengthen training in aquatic rescue as a preventive and educational strategy. The study focused on the design and implementation of a comprehensive program aimed at the development of technical, physical and emotional competencies for emergency care in aquatic spaces, with the purpose of promoting an institutional culture of self-care and social responsibility. The methodology adopted was mixed, incorporating quantitative and qualitative tools. Theoretical, physical and psychological tests were applied before and after the training process, structured in 40% theoretical content and 60% practical. The sample was made up of people with little previous experience, which allowed us to assess the impact of the program from a training perspective. The results revealed a mean theoretical performance (average: 2.69/5), with strengths in protocols such as PRICE (93.75% of correct answers), but weaknesses in resuscitation techniques (93.75% of errors in chest compressions). In physical condition, 56.25% were between "low" and "acceptable" levels in cardiorespiratory tests, and only 25% showed optimal aptitude in the aquatic environment. In the psychological component, 62.5% had a medium level in the state of anxiety, and 37.5% at a high level. It is concluded that the training had a positive impact on the comprehensive preparation of the participants, highlighting its value as a transformative pedagogical practice, with the potential to be integrated into educational contexts that seek to promote safe environments and citizens committed to collective well-being.